Constraints Perceived in Adoption of Improved Practices of Small Scale Dairying: A Gender Analysis - Jyoti Yadav , Hema Tripathi; Anirudha Kumar (Indian Journal of Extension Education, 2013)
The present study was carried out in mid western plain zone of Uttar Pradesh to identify the various constraints perceived separately by female and male headed households in adopting improved practices in small scale dairying. Data were collected through interview schedule from 50 female and 50 male headed households. The study revealed that the major constraints among breeding practices perceived by females and male respondents were same i.e. non functioning of A.I. centre/ill equipped A.I. centre followed by scarcity of resources to maintain crossbred cattle/superior breed of milch animals. Inadequate knowledge about scientific feeding, high cost of ingredients of concentrates mixture and preference to grow cash crops instead of fodder crops were found to be the first, second and third major constraints in both sets of respondents in adoption of improved feeding practices. Lack of knowledge about common contagious diseases, their causes & control measures (Ist), ill equipped veterinary hospitals and lack of facility for treatment, vaccine (IInd) were the constraints perceived by women respondents.